Peramalan Persediaan Bahan Di Forever Hope Digital Printing - Alamsyah, Rizky; Sumirat, Lambang Probo; Kristyawan, Yudi (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2024)
This research aims to develop an inventory forecasting system application at the Forever Hope Digital Printing company. In this research, the Trend Moment and Parabolic Trend methods are used as the application knowledge base for forecasting inventory. The Web-based system was developed using the Laravel framework with the PHP programming language and MySQL database. This system allows administrators to manage sales data, carry out prediction processes, and view stock prediction reports. The test results show that the output of the Inventory Peramalam Application with the knowledge base of the Trend Moment and Trend Parabolic methods is the same as the results of manual calculations using the Trend Moment and Trend Parabolic formulas. This shows that the application can be recommended for use in forecasting inventory at the Forever Hope Digital Printing company, so that it can help in managing inventory operational costs efficiently, and can simplify the inventory management process. The results of this research can also be a reference for other companies that want to develop an inventory forecasting system using the Moment Trend and Parabolic Trend methods.Kata kunci: Forecasting; Moment Trend; Parabolic Trend; Sales; Stock InventoryÂ AbstrakPenelitian ini bertujuan untuk mengembangkan aplikasi sistem peramalan persediaan barang di perusahaan Forever Hope Digital Printing. Dalam penelitian ini, digunakan metode Trend Moment dan Trend Parabolik sebagai basis pengetahuan aplikasi untuk meramalkan persediaan barang. Sistem berbasis Web dikembangkan menggunakan framework Laravel dengan bahasa pemrograman PHP dan database MySQL. Sistem ini memungkinkan administrator untuk mengelola data penjualan, melakukan proses prediksi, dan melihat laporan hasil prediksi stok barang. Hasil pengujian menunjukkan luaran Aplikasi Peramalam Persediaan dengan basis pengetahuan metode Trend Moment dan Trend Parabolik sama dengan hasil perhitungan manual menggunakan formula Trend Moment dan Trend Parabolik. Ini menunjukkan bahwa aplikasi dapat direkomendasikan untuk digunakan dalam meramalkan persediaan barang di perusahaan Forever Hope Digital Printing, sehingga dapat membantu dalam pengelolaan biaya operasional persediaan secara efisien, serta dapat mempermudah proses pengelolaan persediaan barang. Hasil penelitian ini juga dapat menjadi referensi bagi perusahaan lain yang ingin mengembangkan sistem peramalan persediaan barang dengan menggunakan metode Trend Moment dan Trend Parabolik.Â